3D printed zeolite-Y for removing heavy metals from water. (August 2021) - Khalil, Abdullah; Hashaikeh, Raed; Hilal, Nidal
Abstract: Zeolites, in the form of monolithic and well-defined structures, offer great opportunity as potential adsorbents to remediate various environmental pollutants. In this work, zeolite-Y structures were fabricated via 3D printing technique and their potential was demonstrated for removing toxic heavy metals from wastewater. Using a lab-scale column-type configuration, the mesoporous 3D printed zeolite structures were tested as adsorbents for heavy metals such as lead and copper that are known toxic pollutants normally present in the variety of industrial wastewaters. The results indicate that 3D printed zeolite-Y structures can reduce the concentration of lead and copper by more than 90% under optimal pH and low flow rate conditions. In addition, the structures remained stable with a repeatable performance after several water treatment cycles. This study, therefore, demonstrates the potential of 3D printing technology to fabricate zeolites in the desired geometries that can be employed in the continuous flow systems for wastewater treatment and other similar applications. Graphical abstract: Unlabelled Image Highlights: Zeolite-Y was 3D printed using nanoclay as the primary binder. Prolonged 3D printing was possible with excellent geometrical conformance. 3D printed calcined zeolite-Y (3DZC) exhibit mesoporosity and structural integrity. 3DZC was tested for removing heavy metals from aqueous media. More than 90% of Pb and Cu were removed by 3DZC.